1991
DOI: 10.1021/jm00106a027
|View full text |Cite
|
Sign up to set email alerts
|

Design of potent oxytocin antagonists featuring D-tryptophan at position 2

Abstract: We prepared nine analogues (1-9) of MCPA-D-Phe-Phe-Ile-Asn-Cys-Pro-Arg-Gly-NH2, [MCPA1, D-Phe2, Phe3, Ile4, Arg8]oxytocin (MCPA = beta-mercapto-beta,beta-pentamethylenepropionic acid), a potent antagonist of the rat uterotonic action of oxytocin (OT). We replaced D-Phe with D-Trp and made [MCPA1,D-Trp2,Phe3,Ile4,Arg8]OT (1), which had OT pA2 of 7.51, somewhat higher than that of the D-Phe2 antagonist which has OT pA2 = 7.35 in our rat uterotonic assay. Both compounds are equipotent as antagonists of [Arg8]vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 4 publications
1
29
0
2
Order By: Relevance
“…A baboon model was chosen for this study because it forms a single discoid placenta which is similar to the human and different to that of the rhesus monkey, which normally has a bilobed placenta [ 11 ]. A laparotomy was necessary for anchoring the cannulae to the uterine serosa and to tunnel them for protec tion.…”
Section: Discussionmentioning
confidence: 99%
“…A baboon model was chosen for this study because it forms a single discoid placenta which is similar to the human and different to that of the rhesus monkey, which normally has a bilobed placenta [ 11 ]. A laparotomy was necessary for anchoring the cannulae to the uterine serosa and to tunnel them for protec tion.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years a number of OTAs have been synthesized, including oxytocin-derived peptidyl [11][12][13][14][15][16][17], non-oxytocin-derived peptidyl [18], and non-oxytocin-derived non-peptidyl compounds [19,20]. Only recently have laboratories focused on developing OTAs for inhibiting preterm labor in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of the literature, Higby and co-workers [1] concluded that among those tocolytic agents commonly used (i.e., 3-sympathomimetics, MgSO 4 , calcium channel blockers, and indomethacin), only prostaglandin synthesis inhibitors are effective in the treatment of preterm labor. The development of OTAs, both peptidyl [11][12][13][14][15][16][17][18] and non-peptidyl [19,20], as potential tocolytic agents for humans in preterm labor has recently been reported, and clinical evaluation is being performed on several of them [21]. The ideal therapeutic agent for the treatment of preterm labor should be highly specific and have minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stepwise improvement of OT-R binding affinity, and antagonist potency, as well as OT/AVP receptor selectivity [238,239,240], led to a final compound, 18, termed Antag III, or TT-235 [241] [see Fig. (7)], which is reported to have 90-fold higher affinity for the OT-R than atosiban [242], and to be 50-fold more efficacious in a baboon model of uterine contractions [243].…”
Section: Peptide Antagonistsmentioning
confidence: 99%